Gender equity as a key element for agroecological transitions: Neo‐rural women as managers of agroecological initiatives - Beatriz Vizuete; Marina García‐Llorente; Irene Pérez‐Ramírez; Elisa Oteros‐Rozas (People and Nature)
Abstract Gender equity is considered to be a key element for the agroecological transitions of agri‐food systems and sustainable transformation of socioecological systems. Many women have recently become agroecological farmers. Few studies have examined this phenomenon and its potential implications for the agri‐food system and in rural areas, where men's experiences are still considered to be universal, from a gender‐focused perspective. We conducted semi‐structured interviews with 15 women leading agroecological initiatives in the Madrid region and performed content and critical discourse analyses of the interview transcripts to examine: (1) the women's motivations for agroecological project initiation; (2) the influences of the project composition, women's marital status and their trajectories in agroecological initiatives; and (3) the barriers they face and strategies they have developed to overcome difficulties. All interviewees highlighted political and lifestyle motivations, that is, based on environmental and agroecological ideals, such as liking to work closely with nature generating positive impacts on the territory and the pleasure of doing what they wanted. Motivations and barriers varied according to origin; neo‐rural women faced the most difficulties, although all interviewees reported gender‐specific barriers. We propose pathways to integrate the plurality of actors and values and to promote new rural identities that fall from traditional stereotypes to enhance gender equity and move towards a true agroecological transition. Read the free Plain Language Summary for this article on the Journal blog.